2013
DOI: 10.2304/elea.2013.10.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Researching Resistance to Open Education Resource Contribution: An Activity Theory Approach

Abstract: Higher education and associated institutions are beginning to share teaching materials known as Open Educational Resources (OER) or open courseware across the globe. Their success depends largely on the willingness of academics at these institutions to add their teaching resources. In a survey of the literature on OER there are several articles that discuss reasons why academics should contribute teaching materials. There are fewer articles that refer to academics' concerns or why they choose not to contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
(32 reference statements)
1
10
0
1
Order By: Relevance
“…On that note, a number of researchers cite the lack of funding, inaccessibility and inadequate infrastructure to be common contraints for higher education institutions too, which hinder the promotion and sustainability of OERs (Anderson & McGreal 2012;Olcott, 2012a;Olcott 2012b;De Langen & Bitter-Rijkema, 2012;Cohen & Soffer, 2015;Sener, 2010;Joseph & Nath, 2013). Another significant problem associated with OER content creation at the tertiary level is the unavailability and resistance of academics in creating OERs due to time limitations, pedagogical concerns and peer influence (Cox, 2013). In such cases, higher education institutions investing in OERs could potentially benefit from researching and experimenting with user-generated OERs, with Pratham Books as a best practice model to overcome these problems.…”
Section: Resultsmentioning
confidence: 99%
“…On that note, a number of researchers cite the lack of funding, inaccessibility and inadequate infrastructure to be common contraints for higher education institutions too, which hinder the promotion and sustainability of OERs (Anderson & McGreal 2012;Olcott, 2012a;Olcott 2012b;De Langen & Bitter-Rijkema, 2012;Cohen & Soffer, 2015;Sener, 2010;Joseph & Nath, 2013). Another significant problem associated with OER content creation at the tertiary level is the unavailability and resistance of academics in creating OERs due to time limitations, pedagogical concerns and peer influence (Cox, 2013). In such cases, higher education institutions investing in OERs could potentially benefit from researching and experimenting with user-generated OERs, with Pratham Books as a best practice model to overcome these problems.…”
Section: Resultsmentioning
confidence: 99%
“…Agency is an issue that has been underplayed in the activity theory but recent studies have indicated how agency emerges in interactions and that agency lies in the relationship between individuals rather than within the individual [44; 45]. Thus, agency in relation to OER adoption is of interest [26] and therefore we explore agency related to the creation, use and remix of OER.…”
Section: B Theoretical Perspectivementioning
confidence: 99%
“…Activity theory has recently been used in the analysis of sharing OER, but individual motivations need to be explored further [26]. This study aims to examine: 1) What are teachers´ values of OER and what are teachers´ motivations?…”
Section: Introductionmentioning
confidence: 99%
“…This stems from three key issues as identified in her study: pedagogical and quality concerns, as well as influence of colleagues. While academics within a faculty seem to share similar doubts on the purpose, necessity and quality of OERs, they also raise concerns on the additional work hours OER creation would entail and the unfavorable effect OERs could have on their traditional way of classroom teaching (Cox, 2013). The literature reports that primary school teachers have similar concerns.…”
Section: Pedagogy and Awarenessmentioning
confidence: 99%
“…The numerous Kanwar et al (2010), Knox (2013a;2013b), Cox (2013), Cox & Trotter (2016), and Wright & Reju (2012). Even though the results found are generally compatible with previous research, there are some areas where literature is scarce.…”
Section: Implications Of Findingsmentioning
confidence: 99%